The Life and Adventures of Santa Claus - Baum, L. Frank (Saga Egmont, 2021)
A young baby named Claus is found abandoned in a forest. Claus is taken in by Ak, the Master Woodsman of the World and a wood nymph named Necile and has a happy upbringing away from other humans. When Claus moves away, he gains a reputation for kindness towards children, and starts carving toys to give them. The evil Agwas steal the toys as they are stopping the children from misbehaving, forcing Claus to enter homes through chimneys to deliver his gifts. There are plenty more adventures in store for Claus before he becomes Santa Claus, in this delightful festive children’s story from renowned author L. Frank Baum.